The Effect of Professionalism, Organizational Commitment and Career Development on Employee Morale at PT. Citilink Indonesia Bengkulu Branch Office - Andre Afrianda; Tezar Arianto (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the effect of professionalism, organizational commitment and career development on employee morale at PT. Citilink Indonesia Bengkulu Branch Office.Every organization wants employees in their company to have good work loyalty so that organizational goals can be achieved properly. Formulation of the problem 1) Does professionalism affect the performance of PT. Citilink Indonesia Bengkulu Branch Office? 2) Does organizational commitment affect the performance of employees of PT. Citilink Indonesia Bengkulu Branch Office? 3) Does career development affect the performance of employees of PT. Citilink Indonesia Bengkulu Branch Office? 4) Do professionalism, organizational commitment and career development affect the morale of PT. Citilink Indonesia Bengkulu Branch Office? This type of research is a quantitative approach. The method used in this research is descriptive method. The population in this study were all employees of PT Cilitink Bengkulu branch, totaling 35 employees. a sample of 35 people. Based on the research results, professionalism has a positive effect on morale, thus the higher the professionalism, the higher the morale of employees at PT. Citilink Indonesia Bengkulu Branch Office. Organizational commitment has a positive effect on employee morale at PT. Citilink Indonesia Bengkulu Branch Office thus the higher the organizational commitment it will increase the morale of employees at PT. Citilink Indonesia Bengkulu Branch Office. Career development has a positive effect on employee morale at PT. Citilink Indonesia Bengkulu Branch Office thus the higher the career development it will increase the morale of employees at PT. Citilink Indonesia Bengkulu Branch Office. Professionalism, organizational commitment and career development together show a positive influence on morale. The test results show a significance value of <0.05.